Hope, optimism, and pessimism as predictors of positive and negative psychological changes related to the COVID-19 pandemic in Slovak adults - Jurišová, Erika; Pivková, Lucia; Ráczová, Lucia; Sollár, Tomáš; Romanová, Martina (Frontiers in Psychology, 2023)
Background, objectives: Positive and negative changes in outlook represent psychological changes that are results of the cognitive processing of stressful and traumatic event by an individual. Objectives of the study: 1) to determine the level of occurrence and types of positive and negative changes in connection with the COVID-19 pandemic among adults in Slovakia and 2) to study the role personality factors – hope (dispositional and perceived) and life orientation (optimism, pessimism) in the prediction of positive and negative changes in adults during the fourth pandemic wave. Methods: A Short Form of the Changes in Outlook Questionnaire (CiOQ-S), The Dispositional Hope Scale (DHS), Perceived Hope Scale (PHS), and Life Orientation Test (LOT-R) were administered. The research sample consisted of 102 participants, age ranged from 20 to 65 years (Mage= 38.90, SD = 14.28). The research design is quantitative, exploratory, and confirmatory. Results: 95 % of participants reported positive changes related to COVID-19. Concurrently, up to 70 % of these participants reported also negative changes impact of the pandemic. Only 25 % of participants reported positive changes without noticing any negative perception of the consequences of the pandemic. 68 % of participants reported negative changes related to COVID-19. Only 29 % of participants reported negative changes without noticing any positive perception of the consequences of the pandemic. In total, up to 86 % of participants agreed with experienced psychological changes (positive or negative) as a result of the COVID-19 pandemic. High prevalence of positive changes along with relatively high prevalence of negative changes related to the COVID-19 pandemic outlines the question whether reported positive changes represent real or illusory growth. Optimism and pessimism were found to be significant independent predictors of positive changes related to the COVID-19 pandemic. Hope was identified as a significant independent predictor of negative changes related to the COVID-19 pandemic.